Storm warning - Bell, David, 1969 November 17- (Berkley, 2024)
"A man living on a Florida barrier island must protect his family from both an approaching hurricane and a relentless killer. Jacob Powell is racing to get off the island as a hurricane approaches. When he finds his friend Dallas, the building manager, dead from a blow to the skull, Jacob realizes there's more than the hurricane to fear. The murderer is likely still on the island, maybe even inside the nearly abandoned building. Dallas had repeatedly run afoul of the wealthy owners of the building by complaining about code violations and the precarious state of the condos. But he'd also told Jacob that every one of the residents had a secret they'd come to Florida to escape. Had one of them killed to hide it?"--